2018
DOI: 10.3892/ol.2018.8155
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of detecting circulating tumour cells in the peripheral blood of nasopharyngeal carcinoma patients

Abstract: The aim of the present study as to analyse the associations between circulating tumour cells (CTCs) and the clinical parameters of nasopharyngeal carcinoma (NPC). Peripheral blood (7.5 ml) from 68 first-diagnosed NPC patients was collected to detect and identify CTCs by cluster of differentiation (CD)45 immunomagnetic separation. Immunofluorescent staining of cytokeratin-18, CD45 and DAPI, and fluorescence in situ hybridization were combined with the centromere of chromosome 8 (CEP8) probe method to analyse th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Most of the studies revealed that CTC was characterized by CD45-CEP8+cells in NPC [37][38][39]. In this study, CTCs were detected using immunostaining of DAPI, CD45 and CEP8.…”
Section: Discussionmentioning
confidence: 86%
“…Most of the studies revealed that CTC was characterized by CD45-CEP8+cells in NPC [37][38][39]. In this study, CTCs were detected using immunostaining of DAPI, CD45 and CEP8.…”
Section: Discussionmentioning
confidence: 86%
“…CTCs have been explored to be possibly linked to survival [111], although a head‐to‐head comparison by Vo et al. [39] showed that pre‐treatment EBV DNA was better associated to survival than pre‐treatment CTC.…”
Section: Utility Of Ebv Liquid Biopsy In Npc Prognosticationmentioning
confidence: 99%
“…23 In clinical cases of NPC, CTCs were closely associated with NPC stage, with later clinical stages associated with higher CTCpositive rates. 24 Therefore, CTCs may serve as biomarkers for monitoring the therapeutic efficacy of treatments for NPC. 25 Studies have shown that EBV proteins participate in NPC metastasis, 26,27 and recent reports suggested that EBV may be involved in CTC generation.…”
Section: Introductionmentioning
confidence: 99%